Ultrastructural Changes in Candida albicans Induced by Benzyl Isothiocyanate (BITC) - Ana Calado; Cheila Pereira; Ana C. Sampaio (Biology and Life Sciences Forum)
The search for new antifungal substances is increasingly relevant due to growing antifungal resistance. Candida albicans is the most common pathogen yeast in humans, primarily in immuno-compromised individuals. Isothiocyanates, derived from glucosinolates, are compounds with an antimicrobial effect at low concentrations. The purpose of this study was to analyse the ultrastructural changes in three C. albicans isolates after exposure to benzyl isothiocyanate (BITC) at different lengths of exposure time (2.5, 5 and 24 h). Before exposure to BITC, cells presented a regular round or oval shape, with a uniform cell wall. After exposure to BITC, cell wall damage and loss occurred in the three strains. The cells developed extensive indentations, and a band of electrodense material was formed in the cortical cytoplasm. Although, for one isolate, no intact cells were detected, at the highest exposure time, two of the isolates showed a relevant response, regaining almost normal cell shape with nearly complete cell wall recovery. Cell lysis led to the deposition of a melted and unmixed mass with two apparently distinct fractions, the cell wall fraction and the cytoplasmic fraction. The present work demonstrates that, through targeting the C. albicans cell wall, BITC may prove to be a promising antifungal compound.